Cystic dystrophy of the gastric and duodenal wall developing in heterotopic pancreas: an unrecognised entity. Issue 3 (March 1993) - Fléjou, J F; Potet, F; Molas, G; Bernades, P; Amouyal, P; Fékété, F
Abstract : Ten patients in whom cystic dystrophy developed in a heterotopic pancreas of the duodenal (nine patients) or gastric (one patient) wall are reported. All were young or middle aged white men, only two of whom were alcoholic. The symptoms were caused by intestinal or biliary stenosis, or both, secondary to the inflammation and fibrosis. Only endosonography provided strong evidence for the diagnosis in three patients. All patients underwent surgery: a pancreaticoduodenectomy was performed in eight patients. The surgical specimen showed cystic lesions of the gut wall, occurring in inflammatory and fibrous heterotopic pancreatic tissue. The pancreas proper was normal in all patients. It is suggested that cystic dystrophy is an uncommon and serious complication of heterotopic pancreas. Similar cases associated with chronic pancreatitis of the pancreas have been observed and it is suggested that this process could be responsible for some of the chronic pancreatitis encountered in young, non-alcoholic patients.